Effect of disease-modifying therapies on subcortical gray matter atrophy in multiple sclerosis. (March 2020) - Sotirchos, Elias S; Gonzalez-Caldito, Natalia; Dewey, Blake E; Fitzgerald, Kathryn C; Glaister, Jeffrey; Filippatou, Angeliki; Ogbuokiri, Esther; Feldman, Sydney; Kwakyi, Ohemaa; Risher, Hunter; Crainiceanu, Ciprian; Pham, Dzung L; et al.
Background: The effects of disease-modifying therapies (DMTs) on region-specific brain atrophy in multiple sclerosis (MS) are unclear. Objective: To determine the effects of higher versus lower efficacy DMTs on rates of brain substructure atrophy in MS. Methods: A non-randomized, observational cohort of people with MS followed with annual brain magnetic resonance imaging (MRI) was evaluated retrospectively. Whole brain, subcortical gray matter (GM), cortical GM, and cerebral white matter (WM) volume fractions were obtained. DMTs were categorized as higher (DMT-H: natalizumab and rituximab) or lower (DMT-L: interferon-beta and glatiramer acetate) efficacy. Follow-up epochs were analyzed if participants had been on a DMT for ⩾6 months prior to baseline and had at least one follow-up MRI while on DMTs in the same category. Results: A total of 86 DMT epochs (DMT-H: n = 32; DMT-L: n = 54) from 78 participants fulfilled the study inclusion criteria. Mean follow-up was 2.4 years. Annualized rates of thalamic (−0.15% vs −0.81%; p = 0.001) and putaminal (−0.27% vs −0.73%; p = 0.001) atrophy were slower during DMT-H compared to DMT-L epochs. These results remained significant in multivariate analyses including demographics, clinical characteristics, and T2 lesion volume. Conclusion: DMT-H treatment may be associated with slower rates of subcortical GM atrophy, especially of the thalamus and putamen. Thalamic and putaminal volumes are promising imaging biomarkers in MS.